A group show - Theys, Hans; Dings, Maarten; Naudts, Joachim; Van Herreweghe, Egon; Wolkman, W.; Exhibition Ghent. croxhapox 2010-09,4 ([Gent] : [s.n.], 2010)
An exhibition curated by RE: with Edward Clydesdale Thomson (UK), Sara Deraedt (BE), Eva-Fiore Kovacovsky (CH), Anouk Kruithof (NL), Alexandra Leykauf (DE), Valérie Mannaerts (B), Michèle Matyn (BE), Saskia Noor van Imhoff (NL), Jimmy Robert (FR), Dominique Somers (BE), Tania Theodorou (GR), Kathleen Vinck (BE), Claudia Weber (DE) & Wesley Wim Wolkman (BE)
"Published on the occasion of the exhibition A Group Show (4 till 26 September 2010) Organized by Punctum at croxhapox, Ghent, Belgium.
Teksten in Nederlands en Engels
boek